Easy Access to Energy Fluctuations in Nonequilibrium Quantum Many-Body Systems (2021)
We combine theoretical and experimental efforts to propose a method for studying energy fluctuations, in particular, to obtain the related bistochastic matrix of transition probabilities by means of simple measurements at the end of a protocol that drives a many-body quantum system out of equilibrium. This scheme is integrated with numerical optimizations in order to ensure a proper analysis of the experimental data, leading to physical probabilities. The method is experimentally evaluated employing a two interacting spin-1/2 system in a nuclear magnetic resonance setup. We show how to recover the transition probabilities using only local measures, which enables an experimental verification of the detailed fluctuation theorem in a many-body system driven out of equilibrium